Plan de gestión para el desarrollo de una máquina liofilizadora para la empresa ATECSA - Chan-Cheng, Victor (Instituto Tecnológico de Costa Rica, 2015)
ATECSA was founded in 2008. Initially, the company was dedicated to provide engineering services to various manufacturing companies. In 2012 the administration decided to focus on a different business model and switched to manufacturing of food products. The company developed a product line called Kilwó, which consists of dried fruits manufactured by a chemical freeze-drying process called lyophilization. ATECSA wishes to carry out the design and construction of a machine that allows them to increase production capacity and reduce electricity and maintenance costs. The final project goal is the design of a lyophilization machine processes based on the needs of the company and the delivery of their respective electrical and mechanical drawings plans used for its construction. The economic risk to the company is high if the project fails and will delay its expansion plans in the local market. The development of this type of machine carries a design risk due to its involvement in different engineering areas that needs to be complemented one another to obtain the product with the requirements of the company, to mitigate this risk, it is decided to apply the use of systems engineering process to plan the scope of multidisciplinary projects and the methodology of project management to increase the probability of success for the project. The main objective of this graduation project is to develop a project management plan for the design and construction of a freeze-drying machine that meets the predefined product requirements requested by ATECSA documented in the Project Charter. The final conclusion of the project is summarized in the following point: the necessary plans, processes and tools were developed, according to the methodological guide PMBoK®, which will complement a plan to manage the project of a lyophilizer machine. The final recommendations suggest that ATECSA .should update their .scope plan with the feedback and information provided by the team work when the resources required for the project had been hired, it’s also necessary to specify in the job offer that each professional should follow the communications plan previously defined by the project management plan. Keywords: Lyophilization, Project Management, Systems Engineering, Financial Flows, PMI, Management Plan, ATECSA.
Proyecto de Graduación (Maestría en Gerencia de Proyectos) Instituto Tecnológico de Costa Rica. Escuela de Administración de Empresas, 2015.
Keywords: Gestión de proyectos; Ingeniería; Proyectos financieros; Gestión; Administración; Manufactura